FREQUENCY OF PERIPHERAL NEUROPATHY IN PATIENTS WITH DIABETES MELLITUS - Iftikhar, Mehwish; Hussain, Azhar; Rizvi, Amina (Journal of Ayub Medical College Abbottabad, 2014)
Background: The main purpose of this study was to ascertain the frequency of peripheral diabetic neuropathy in diabetic patients and to stratify the different variants of peripheral neuropathy in patients. Methods: Two hundred and fifty diabetic patients presenting to diabetic management centre, were included in this cross sectional study. Effect modifier (duration of diabetes) were studied through stratification. Eleven point neuropathic pain scale was used to access the extent of neuropathy. Results: The frequency of neuropathy in diabetic patients was 187 (74.8%). Out of 250 patients 116 (46.4 %) patients were found to have burning type of pain and 114 (45.6%) were found to have numbness while 61 (24.4%) had tingling. Out of 250 patients 17 (6.8%) were found to have sharp pain and 55 (22%) had dullness. Out of 250 patients 44 (17.6%) had coldness. Ten patients (4%) out of 250 had sensitive type of pain. frequency of itchy type of pain was 6.4%. Conclusion: The study showed that painful diabetic neuropathy is present in majority of controlled diabetics and most of them belong to old age. It further showed that majority of sufferer were females. The most common variety of pain encountered was burning type of pain. Keywords: Diabetes mellitus, Diabetic peripheral neuropathy